Insurance Claims For Loss Of Goods (study decision number 16/Pdt.G.S/2022/PN Mks) - Angelline Putri Permatasari (International Journal of Law and Legal Ethics, 2025)
Insurance or coverage is something that is no longer foreign to the Indonesian people, where most Indonesian people have entered into insurance agreements with insurance companies, both state-owned and private insurance companies. Insurance companies are non-bank financial institutions that have a role that is not much different from banks, namely engaged in the field of service services provided to the community in overcoming risks that occur in the future. Insurance is very important because in addition to providing protection against possible losses, insurance also encourages other economic growth. The method used in this study is the normative juridical method. The results of the study show that claims in insurance terms are interpreted as requests or demands for payment of benefits in accordance with the provisions stipulated by the insurance policy. A claim is an application by a participant to obtain coverage for losses available based on the agreement. The claim process steps for each insurance company are different, but basically the process is carried out by the insured by submitting a claim to the insurer which will then be processed whether the process rights are approved or not approved. Unfortunately, in practice, the guarantee of legal protection for insurance policyholders is less protected. The problem that is always experienced by policyholders is the difficulty of obtaining compensation payments when an event occurs. Thus it can be said that default is the implementation of obligations that are not fulfilled or broken promises or negligence carried out between the parties either because they do not carry out what has been agreed or even do something that according to the agreement should not be done. There are ways that can be taken to resolve disputes between the parties involved in a dispute, namely through litigation and non-litigation.